2017
DOI: 10.1177/0009922817730343
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Administered Screening Tool May Improve Detection and Diagnosis of Depression Among Adolescents

Abstract: Depression among adolescents is underdiagnosed and associated with significant morbidity and mortality. The American Academy of Pediatrics endorses opportunistic depression screening beginning at age 11, implying that screening should be performed at every visit. The purpose of this quality improvement project was to determine whether a self-administered depression screen would improve the identification of major depressive disorder among adolescents in a pediatric primary care clinic. Introduction of the Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…A similar study done in a rural clinic in South Carolina showed a compliance rate of 88% for administering depression screen in the adolescent population. 11 A study done in Michigan showed screening rate of 82%. Researchers were able to integrate the depression screening questionnaire into the clinic's EHR which made the screening process easier and also served as a reminder for the physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study done in a rural clinic in South Carolina showed a compliance rate of 88% for administering depression screen in the adolescent population. 11 A study done in Michigan showed screening rate of 82%. Researchers were able to integrate the depression screening questionnaire into the clinic's EHR which made the screening process easier and also served as a reminder for the physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that implementing PHQ-A in a paediatric primary care setting led to increased diagnosis of depression among adolescents. 11 Major depressive disorder has short-term effects that include poor school performance, suboptimal growth and development, behavioural changes and impairment in normal interaction with family members and peers. Some of the long-term consequences include poor education rates that lead to low socioeconomic status, aggressive behaviour, the diagnosis of depression and anxiety in adulthood, increased risk for self-injurious behaviour and suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, implementing routine screening of depression in the PHC setting improved detection of depression [45,46,49,56]. These improvements did not mostly have statistical and practical signi cance.…”
Section: Effectiveness Of Screening Interventions With or Without Fee...mentioning
confidence: 96%
“…Regarding studies which evaluated screening/feedback interventions, several types of screening tools were used, including different versions of the Patient Health Questionnaire (PHQ) [45][46][47][48][49], Zung Selfrating Depression Scale (SDS) [47,50], Quick Inventory for Depression Symptomatology Self-report (QIDS-SR) [51], General Health Questionnaire (GHQ) [52][53][54][55], Edinburgh Postnatal Depression Scale (EPDS) [56], and Primary Care Evaluation of Mental Disorders (PRIME-MD) [57] (Table 3). Nevertheless, PHQ and GHQ were the most commonly used screening tools.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…EDs also have an increasing role for initiating follow-up care to reduce subsequent crises [3] [4]. Recent studies reveal usefulness of such questionnaires in detection of depressive status and suicide ideation of adolescents [5] [6]. The lack of determination of patient with high risk for re-suicidal attempt may result in undesired clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%